Nutritional effects on beef palatability - Burson, D.E.; Hunt, Melvin C.; Hayward, L.H.; Kastner, Curtis L.; Kropf, Donald H.; Allen, Dell M. (Kansas State University. Agricultural Experiment Station, 2011)
We assigned 112 Angus yearling steers to 14 nutritional treatments including control. Submaintenance, and 12 different combinations of ration energy (low, medium or high) and feeding period (56,91, 119, 147, or 175 days). Boneless rib steaks were evaluated by a trained taste panel and Instron Warner-Bratzler shear. Average daily gains increased as energy level increased. Slaughter weight, and USDA quality and yield grades increased as both ration energy and days fed increased. Taste panel score were not significantly affected by ration energy level, but muscle fiber tenderness, juiciness, flavor and overall tenderness scores tended to increase as days fed increased. Peak shear force was no affected by ration energy level or days fed.
Keywords: Beef; Palatability; Average daily gain; Energy